The Emperor's New Clothes: A Critique of the Current WHO Classification of Malignant Melanoma. (December 2020) - Weyers, Wolfgang
Abstract : Abstract: The World Health Organization's classification of skin tumors of 2018 presents melanoma as a loose assembly of independent biologic entities, each of which is characterized by a distinctive constellation of clinical, histopathologic, and molecular findings that evolve through different pathways of lesional progression from a benign to an intermediate and, ultimately, malignant tumor. The alleged pathways, however, are based on vague correlations and fail to take into account the common occurrence of lesions that cannot be assigned to either of them. Moreover, there is no such thing as a lesional progression. The evolvement of neoplasms is always a clonal and, therefore, initially focal event. In the majority of melanomas, there is no evidence of a juxtaposition of a benign, intermediate, and malignant portion. Occasionally, a melanoma may develop within the confines of a melanocytic nevus, but a nevus cannot transform into melanoma. The concept of lesional progression merely serves to handle problems of differential diagnosis because it obscures and, in fact, denies the difference between benign and malignant neoplasms. In the current classification of the World Health Organization, every lesion is said to bear some risk of malignant progression, intermediate categories are recognized for all alleged pathways, and no distinction is made between "high-grade dysplasia" and melanoma in situ. Differentiation between benign and malignant neoplasms of melanocytes may be difficult, but the concept of lesional progression does not address those problems; it merely offers evasions under the disguise of diagnoses.